Growth performance and carcass quality of different breeds and diets with identification of possible molecular protein biomarker as a stress indicator in slaughtered village chicken / Mohd Shahmi Hakimi Mazlishah - Mohd Shahmi Hakimi, Mazlishah (2019)
The development of village chicken industry in Malaysia is still slow despite of high demand from consumers. Factors that contribute to the slow progress are due to the feed management, breed selection and farm management. The objectives of this research were to evaluate the effect of different breeds and diets on the growth performance and carcass quality of village chicken. In addition, the effect of stress during slaughtering on possible molecular protein biomarker was identified. Two (2) strains of village chicken, which were purebred (PVC)(n=100) and crossbred (CVC)(n=300) were reared and fed on 2 types of diet, namely commercial finisher diet (CFD) and formulated finisher diet (FFD). In Experiment 1, the body weight and feed intake were measured weekly and carcass evaluation was done at 2 slaughter ages for each strain, which were (PVC: on Weeks 12 and16) and (CVC: on Weeks 8 and 12. In Experiment 2, the quality of crossbred village chickens were determined by using molecular approach to identify stress occurrence resulted from slaughtering by using 2 slaughtering methods, namely Non-stress slaughtering method (NSSM) and stress slaughtering method (SSM). Glutathione-S-transferases expression and activity was measured and observed using proteomic approached. Generally, the body weight for CFD fed chicken for both strains showed no significant differences with FFD. Male CFD was significantly heavier compared to male FFD fed chicken. However, in crossbred village chicken, female CFD and FFD showed no significant differences across the weeks in terms of body weight. PVC recorded high feed conversion ratio (FCR) for feed, CFD (2.9) and FFD (5.2), whereas CVC recorded lower FCR for CFD (2.4) and FFD (2.6). It is suggested when fed with FFD, the feed conversion ratio for CVC would be better than for PVC, probably due to the former were well adapted and efficient utilisation of this formulated feed, thus resulting in faster growth and productive FCR. Interestingly, carcass evaluation showed that the meat to bone percentage for FFD fed chicken in both strains was higher compared to chicken fed on CFD, however no significant difference was detected in absolute meat quantity between CFD and FFD in both strains of village chicken. This is indicating that CFD develop more bone mass. In CVC, FFD fed chicken showed significantly higher in crude protein (84.5±1.1%) compared to CFD (78.4±2.5%), moreover, CFD recorded significantly higher in ash content (9.4±1.6%) compared to FFD fed chicken meat (5.3±0.4%). Besides, in PVC, FFD fed chickens showed significantly higher in crude fibre content (5.2±3.1%) compared to CFD (2.4±1.8%). Amino acid profile was analysed, where 12 amino acids showed significantly higher in FFD fed chicken’s meats than CFD, which indicating high nutritive value of the meat. Generally, amino acid contents in the CVC given CFD and FFD were higher compared to amino acid in commercial broilers and other indigenous chicken. There were significant differences in GSTs activity between NSSM and SSM indicating SSM method could induced oxidative stress. In conclusion, FFD chicken produced higher nutritive value meat compared to CFD chicken as shown the data of proximate and amino acid. Although FFD result in higher FCR, but the cost of the feed was lower and producing high quality of village chicken.